Decreasing academic stress through problem-focused coping strategy for junior high school students - Mujahidah, Nurma Eliya; Astuti, Budi; Nhung, Le Ngoc Ai (Research and Social Study Institute, 2019)
The study aims at identifying the influence of the problem-focused coping strategy on academic stress decrease of VIII Grade students in junior high schools. The study is a quantitative research using quasi-experimental design with non-equivalent control group design. During the conduct of the study, the population of the participants was 180 students and the samples were gathered from the population by means of purposive sampling technique. The total number of the sample was 10 students, consisting of 5 students as the members of the experimental group and 5 students as the members of the control group. Then, the instrument that had been implemented in the group was the academic stress scale. On the other hand, the data analysis technique that had been implemented in the study was the non-parametric statistics namely the Wilcoxon test. The results of the study show that the problem-focused coping strategy has influence on academic stress decrease with the rate of significance 5% (sig. = 0.042, p < 0.05). Therefore, it might be safely concluded that the problem-focused coping strategy has influence on the academic stress decrease among the Grade VIII students in junior high schools.